The Impact of CEO Tenure, Capital Structure, Stock Prices on Firm Value (Empirical Study on the Automotive Industry and Components listed on the Indonesia Stock Exchange for the 2013-2019 Period) - et. al., Yati Mulyati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Influence of CEO Tenure, Capital Structure, Stock Price on Firm Value (Empirical Study on Automotive Industry and Components listed on the Indonesia Stock Exchange 2013-2019 Period). This study aims to examine empirically the effect of CEO tenure, capital structure and stock prices on firm value. The independent variables in this study are the effect of CEO as X1, Capital Structure as X2, and Stock Price as X3. The dependent variable is the value of the company as Y. This type of research takes time series and cross section data in the automotive industry and the 2013-2017 observation period. The number of research samples using purposive sampling technique, namely obtained 77 samples. The data analysis used was t test (partial) using Eview 10. The results showed that CEO tenure and stock prices had an influence on firm value, while capital structure had no effect on firm value.